Strategies and Challenges in Promoting Teacher Discipline: Insights from Vocational High Schools in Indonesia - Kamaruzzaman, Kamaruzzaman; Bahrun, Bahrun; Khairuddin, Khairuddin (Journal of Educational Management and Learning, 2025)
This study investigates the role of principals in promoting and sustaining a disciplined culture among teachers in vocational high schools within West Aceh District, Indonesia. Employing a qualitative, descriptive research design, the study focuses on three main objectives: examining the specific disciplinary programs implemented by principals, exploring how these initiatives are evaluated for effectiveness, and identifying the challenges principals face in ensuring consistent discipline among teachers. Data were collected through open-ended questionnaires distributed to teachers and semi-structured interviews conducted with principals, enabling a comprehensive understanding of both perspectives. Thematic analysis revealed that principals prioritize structured program implementation and regular evaluation as key strategies for managing discipline. Despite overall positive responses to the effectiveness of these initiatives, teachers highlighted several challenges, including inconsistent policy enforcement and varying levels of commitment, which hinder the establishment of a cohesive disciplinary environment. The findings suggest that while principals play a crucial role in shaping discipline, addressing specific challenges through additional resources and teacher engagement could further enhance policy adherence and effectiveness. This study provides valuable insights into the impact of leadership on school discipline and offers recommendations to strengthen disciplinary practices in vocational education settings.